Irisin at the crossroads of inter-organ communications: Challenge and implications - Zhao, Renqing (Frontiers in Endocrinology, 2022)
The physiological functions of organs are intercommunicated occurring through secreted molecules. That exercise can improve the physiological function of organs or tissues is believed by secreting myokines from muscle to target remote organs. However, the underlying mechanism how exercise regulates the inter-organ communications remains incompletely understood yet. A recently identified myokine–irisin, primarily found in muscle and adipose and subsequently extending to bone, heart, liver and brain, provides a new molecular evidence for the inter-organ communications. It is secreted under the regulation of exercise and mediates the intercommunications between exercise and organs. To best our understanding of the regulatory mechanism, this review discusses the recent evidence involving the potential molecular pathways of the inter-organ communications, and the interactions between signalings and irisin in regulating the impact of exercise on organ functions are also discussed.